Task-depending operation and construction of movement systems. Part A: the human leg - Blickhan, R.; Seyfarth, A.; Fackelmayer, P.
Following issues are addressed in this project: - Properties of the leg during different tasks (cyclic and non-cyclic, starts and stops) - The requirements to the musculo-tendonous design to fulfil different tasks - Adaptation of the system to different loading conditions